A Review of Challenges and Security Risks of Cloud Computing - Algubelly Yashwanth Reddy,; P. Hasitha Reddy, (AG Volumes, 2022)
Because of its capacity to cut processing expenses, cloud computing is now one of the most hotly debated topics in the field today. The most intriguing and alluring technology of the present day is that which provides its customers with the ability to request services online. Because cloud computing stores as well as disseminates data in an environment, security has emerged as the primary impediment to the widespread use of the cloud computing settings. Many people utilise cloud to store our personal data, which necessitates a high level of the data storage security over media. When data is being uploaded to a cloud server, security is a key issue. The security dangers and problems of cloud computing are examined in just this review article, which also examines the security standards for cloud computing. Accordingly, the main purpose of this analysis is to categorise cloud computing security threats and issues.